The regional equilibrium in Cameroon. Social equity policy or ethnic drift - Som 1, Joseph Désiré (Transylvznian Review, 2018)
The policy of quotas for access to the civil service, also called ethnicity balance policy, is a controversial subject that crystallizes the ethnic and political tensions in Cameroon. It is understood by most Cameroonians as a premium to certain ethnic groups to the detriment of other ethnic groups. It was established in Cameroon in the early 1980s with the mission of contributing to the building of the Cameroonian nation. We analyze the policy of quotas of access to the civil service in Cameroon to understand its origin, the meaning, and the way in which it is perceived and. evaluated by the Cameroonians. From a comparative sociohistorical approach to politics, far from culturalist approaches, we approach regional equilibrium as a mechanism for public action. Our text is based on the analysis of various sources of archive, as well as on a survey of 257 Cameroonians resident in Cameroon and abroad.
Keywords: Cameroon; ethnicity ethnic quota policy; national unity; regional equilibrium; ⛔ No DOI found